Fly ash as a sorbent for boron removal from aqueous solutions: Equilibrium and thermodynamic studies. Issue 12 (12th August 2020) - Ulatowska, Justyna; Polowczyk, Izabela; Bastrzyk, Anna; Koźlecki, Tomasz; Sawiński, Wojciech
ABSTRACT: This study presents the application of fly ash from brown coal and biomass burning power plant as a sorbent for the removal of boron ions from an aqueous solution. The adsorption process efficiency depended on the parameters, such as adsorbent dosage, pH, temperature, agitation time and initial boron concentration. The experimental data fitted well with the Freundlich isotherm model and the maximum capacity was found to be 16.14 mg g −1 . The adsorption kinetics followed the pseudo-second-order model. Also, the intra-particle diffusion model parameters were calculated. Thermodynamic parameters such as change in free energy ( ΔG° ), enthalpy ( ΔH° ), entropy ( ΔS° ) revealed on exothermic nature of boron adsorption onto the fly ash.